Study on Phase Equilibrium of Ternary System Na+, NH4+ //Cl– -H2O at 0, 10 and 60 °C - Qi, M.M.; Cao, H.X.; Su, M.; Cheng, X.X.; Cao, Y.Y.; Zhang, L. (Asian Journal of Chemistry, 2015)
By means of laser monitoring technology, the solubility data of NaCl and NH4Cl in water at different temperatures were obtained accurately. Solid-liquid phase equal relationship of ternary water-salt system of Na+, NH4+//Cl–-H2O was studied at 0, 10 and 60 °C using moist solid method and phase diagram was drawn. It can provide a theoretical basis for predicting dissolution, evaporation, crystallization, cooling and separation process of water-salt ternary system. The recovery of sodium chloride and ammonium chloride by thermal method were analyzed to provide reference for selecting industrial production conditions.